Application of a mathematical model for the Motoman MH-50 industrial robot’s electric drive system - Vladimirovich Litsin, Konstantin; Rakhmanov, Rakhmetolla; Vitalievich Tsukanov, Andrey (IAES International Journal of Robotics and Automation (IJRA), 2023)
In recent years, there has been a great interest in the transition to digital and automation services for dangerous and menial working processes. Due to its MH50-35 industrial robot, Motoman's properties allow us to improve the control system of an electric drive for industrial robots. The structure of the electric drive for six-axis robot manipulator performance can be superior to conventional Drive Control servos for motor excitation, and a novel automation system can be implemented for its servo performance. To solve these issues, we propose an optimization strategy that allows us to achieve an increase in productivity and labor safety in the industry, reduce the percentage of defects, guarantee product uniformity, and reduce the prime cost of production of items. Ideal conditions were anticipated using a mathematical model. In this study, by using a statistical model, the ideal conditions were synthesized. The optimization of the control system of an electric drive for industrial robot analysis was carried out, and our findings suggest using this model in industrial production to elucidate problems such as high accuracy and speed indicators.